ปัจจัยชี้วัดความเข้มแข็งทางด้านเศรษฐกิจและสังคมของชุมชนริมคลองแสนแสบ ตามหลักปรัชญาเศรษฐกิจพอเพียง (THE ECONOMIC AND SOCIAL STRENGTH OF COMMUNITIES ALONG SAEN SAEB CANAL BY APPLYING PHILOSOPHY OF SUFFICIENCY ECONOMY) - Anupunpisit, Vipavee; Suwandee, Senee; Ratanamaneichat, Chiratus; Annunnum, Ravadee; Mentara, Pavana; Nimnoun, Asanee (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2012)
การวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาปัจจัยชี้วัดข้อมูลทางด้านเศรษฐกิจและสังคมของชุมชนริมคลองแสนแสบ ในการใช้หลักปรัชญาเศรษฐกิจพอเพียง และเพื่อวิเคราะห์ความเข้มแข็งทางด้านเศรษฐกิจและสังคมของชุมชนริมคลองแสนแสบ โดยใช้มิติองค์ประกอบของทุนชุมชน และระดับการใช้ปรัชญาเศรษฐกิจพอเพียงในชุมชน เป็นการวิจัยเชิงสำรวจ (Survey Research) ประชากร คือ ประธานชุมชนหรือผู้ใหญ่บ้านในแต่ละชุมชน/หมู่บ้าน และสมาชิกในแต่ละครัวเรือนในชุมชนบริเวณพื้นที่ริมคลองแสนแสบ ตัวแปรอิสระ คือ 1) ทุนชุมชน 5 ทุน (ทุนกายภาพ ทุนมนุษย์ ทุนสังคม ทุนการเงิน และทุนธรรมชาติ) และ 2) แนวคิดเศรษฐกิจพอเพียง 4 ด้าน (ความพอประมาณ ความมีเหตุผล ภูมิคุ้มกัน และความรู้และคุณธรรม) ตัวแปรตาม คือ ระดับความเข้มแข็งทางเศรษฐกิจและสังคมของชุมชน พื้นที่วิจัยแบ่งเป็น 4 เขต คือ กรุงเทพชั้นใน (ตั้งแต่คลองมหานาค-คลองตัน) กรุงเทพชั้นกลาง (ตั้งแต่คลองตัน-ตลาดมีนบุรี) กรุงเทพชั้นนอก(ตั้งแต่ตลาดมีนบุรี-หนองจอก) และเขตอำเภอบางน้ำเปรี้ยว (ตั้งแต่หนองจอก-คลองบางขนาก) ผลการวิจัยพบว่า เขตกรุงเทพชั้นนอกมีทุนมนุษย์ ทุนการเงิน และทุนกายภาพมากที่สุด ในเรื่องการเข้าถึงข้อมูลข่าวสารความรู้ที่จำเป็น รายได้ประจำและรายจ่ายต่อเดือนของครัวเรือนมีมิเตอร์ไฟฟ้าและน้ำประปาของตนเอง (ตามลำดับ) เขตอำเภอบางน้ำเปรี้ยว จังหวัดฉะเชิงเทรา มีทุนสังคม และมีทุนธรรมชาติมากที่สุด ในเรื่องระยะเวลาการอาศัยอยู่ในชุมชน และการใช้คลองฯเพื่อให้เกิดประโยชน์ และ มีความหนาแน่นของครัวเรือนน้อย ไม่แออัด (ตามลำดับ) สำหรับเขตกรุงเทพชั้นในและชั้นกลาง มีทุนมนุษย์ ทุนสังคม ทุนกายภาพและทุนธรรมชาติน้อยที่สุด เรื่องจำนวนสมาชิกที่อยู่ในวัยทำงาน ระดับการศึกษา การเข้าถึงข้อมูลข่าวสารความรู้ที่จำเป็นและประเพณีของชุมชน ระยะเวลาการอาศัยอยู่ในชุมชน มีปัญหาทางธรรมชาติ และความหนาแน่นของครัวเรือน (ตามลำดับ) ระดับการใช้เศรษฐกิจพอเพียงในชุมชนริมคลองแสนแสบ พบว่า เขตกรุงเทพชั้นนอกมีการใช้เศรษฐกิจพอเพียงในชุมชนสูงที่สุด ในทุกๆ ด้าน ได้แก่ ความพอประมาณ ความมีเหตุผล ภูมิคุ้มกัน ความรู้ และคุณธรรม ระดับความเข้มแข็งของเศรษฐกิจชุมชน พบว่า เขตกรุงเทพชั้นนอกมีค่าสูงสุดอันเนื่องมาจากทุนของชุมชนที่มีอยู่ในระดับสูง อีกทั้งยังมีนำแนวคิดเศรษฐกิจพอเพียงไปประยุกต์ใช้กับกิจกรรมทางเศรษฐกิจต่างๆ อย่างไรก็ตามระดับความเข้มแข็งนี้ ยังสามารถพัฒนาให้เข้มแข็งขึ้นไปได้อีก ในขณะที่ระดับความเข้มแข็งของเศรษฐกิจชุมชนของเขตกรุงเทพชั้นใน เขตกรุงเทพชั้นกลาง และเขตจังหวัดฉะเชิงเทราอยู่ในระดับที่ใกล้เคียงกัน ค่อนข้างต่ำ คำสำคัญ: ความเข้มแข็งทางด้านเศรษฐกิจและสังคมของชุมชน ทุนชุมชน แนวคิดเศรษฐกิจพอเพียง The objective of this research is to study the economic and social indicators of community along Saen Saeb canal by using the philosophy of sufficiency economy. Also, this research aims to analyze the economic and social strength of communities along Saen Saeb Canal using the elements of community capital and the philosophy of Sufficiency Economy in the community level. This is a survey research paper, which has community’s leaders and representatives of each family in communities along Saen Saeb canal being population. The independent variables are: 1) capital community classified into five elements (physical capital, human capital, social capital, financial capital, and nature capital) and 2) the philosophy of sufficiency economy measured in 4 aspects (moderation, reasonable thinking economic immunity, and knowledge and ethics). The dependent variable is the degree of the economic and social strength of communities. Research area is divided into four sub areas: inner Bangkok. (from Mahanak canal - Khlong Tan), in middle Bangkok (from Khlong Tan-Minburi market) and outer Bangkok (from Minburi market-Nong Chok) and Bangnampreaw district (from Nong Chok-Bang Kanag canal). The study found that outer Bangkok has the highest level of human capital, financial capital and physical capital comparing with the other three sub areas. This result came from the easiness of in terms of access to necessary information and knowledge required, high level of income per household, having its own electricity and water supply. On the other hand, Bangnampreaw district has the highest social capital and nature capital, which are resulted from the long period of people living in the community and the Saen Saeb canel utilization, the accurate density of households, respectively. Besides, the research showed that inner Bangkok and middle Bangkok have the lowest levels of human capital, social capital, physical capital and nature capital in terms of education, access to necessary information, knowledge required, community traditions, duration of living in the community, environmental problem and density of households. Considering the level of sufficiency economy in the communities along Klong Saen Saeb, the result demonstrated that people living in outer Bangkok always apply this philosophy in all aspect of their daily life: moderation, reasonable thinking economic immunity, and knowledge and ethics. Consequently, the high levels of community capital and sufficiency economy in the outer Bangkok yield the highest level of economic community strength. However, this strength could be developed. In contrary, the strength of the economic community of inner Bangkok, middle Bangkok and Bangnampreaw district are similarly low. Keywords: economic and social strength of communities, community capital, philosophy of sufficiency economy